2022
DOI: 10.3389/fpsyg.2022.908041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Traditional Chinese Fitness Exercises on Negative Emotions and Sleep Disorders in College Students: A Systematic Review and Meta-Analysis

Abstract: BackgroundThe purpose of this study was to systematically review the effectiveness of regular traditional Chinese fitness exercises on negative emotions and sleep disorders in college students, and to provide evidence-based evidence and new ideas for the negative emotions and sleep disorders among the college students.MethodsA systematic search using 5 English (PubMed, Embase, Scopus, EBSCO, and the Cochrane Library) and 4 Chinese (CNKI, WanFang, VIP, and CBM) databases were initiated to identify randomized co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Of the 19 included systematic reviews, 26 % ( n = 5) ( Bolinski et al., 2020 ; Huber et al., 2022 ; Lin et al., 2022 ; Luo, Zhang, Liu, Ma & Jennings, 2022 ; Oliveira Silva et al., 2023 ) studies were rated as “high”, 26 % ( n = 5) ( Gong et al., 2023 ) ( Yang, Guo, Cheng & Zhang, 2022 ) ( Harrer et al., 2019 ; Huntley et al., 2019 ; Ma, Zhang & Cui, 2019 ) as “moderate”, 37 % ( n = 7) ( Chandler et al., 2022 ; Du et al., 2022 ) ( Chen et al., 2021 ; Lo et al., 2018 ; Luan et al., 2022 ) ( Huang, Nigatu, Smail-Crevier, Zhang & Wang, 2018 ; Song, Liu, Huang, Wu & Tao, 2021 ) as “low” and 11 % ( n = 2) ( Regehr, Glancy & Pitts, 2013 ; Zhang, Li & Wang, 2022 ) as “critically low” quality with the AMSTAR2 scoring system. Supplementary Table 1 presented the details of the quality of each included study evaluated using the AMSTAR2 tool.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 19 included systematic reviews, 26 % ( n = 5) ( Bolinski et al., 2020 ; Huber et al., 2022 ; Lin et al., 2022 ; Luo, Zhang, Liu, Ma & Jennings, 2022 ; Oliveira Silva et al., 2023 ) studies were rated as “high”, 26 % ( n = 5) ( Gong et al., 2023 ) ( Yang, Guo, Cheng & Zhang, 2022 ) ( Harrer et al., 2019 ; Huntley et al., 2019 ; Ma, Zhang & Cui, 2019 ) as “moderate”, 37 % ( n = 7) ( Chandler et al., 2022 ; Du et al., 2022 ) ( Chen et al., 2021 ; Lo et al., 2018 ; Luan et al., 2022 ) ( Huang, Nigatu, Smail-Crevier, Zhang & Wang, 2018 ; Song, Liu, Huang, Wu & Tao, 2021 ) as “low” and 11 % ( n = 2) ( Regehr, Glancy & Pitts, 2013 ; Zhang, Li & Wang, 2022 ) as “critically low” quality with the AMSTAR2 scoring system. Supplementary Table 1 presented the details of the quality of each included study evaluated using the AMSTAR2 tool.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 meta-analyses assessed the effects of exercise interventions including Baduanjin, Taichi, Wuqinxi, traditional Chinese exercises, and aerobic exercise on mental illness, of which 7 ( Du et al., 2022 ; Lin et al., 2022 ; Song et al., 2021 ; Yang et al., 2022 ) meta-analyses related to depression, 7( Du et al., 2022 ; Lin et al., 2022 ; Luo et al., 2022 ; Song et al., 2021 ; Zhang et al., 2022 ) related to anxiety and 1( Lin et al., 2022 ) related to mood changes. 10 re-analyses were nominally statistically significant under random effects models ( P <0.05), however, only one 95 % prediction interval excluded the null value.…”
Section: Resultsmentioning
confidence: 99%
“…They combine balance and coordination capacity on the basis of aerobic exercise and emphasise the physical–psychological connection 38. Because of this, these traditional sports are very popular among people of all ages in China and have become quite popular around the world in recent years 39. Evidence has demonstrated the effectiveness of TCEs in improving cardiopulmonary and musculoskeletal system function and quality of life in older adults 13 14 23.…”
Section: Discussionmentioning
confidence: 99%
“…38 Because of this, these traditional sports are very popular among people of all ages in China and have become quite popular around the world in recent years. 39 Evidence has demonstrated the effectiveness of TCEs in improving cardiopulmonary and musculoskeletal system function and quality of life in older adults. 13 14 23 A number of studies have found TCEs to have a positive effect in increasing BMD, relieving pain, improving muscle mass and preventing falls in patients with OP.…”
Section: Open Accessmentioning
confidence: 99%
“…Chinese traditional fitness exercises are aerobic exercises, guided by medical theories; it pays attention to the unity of mind, breath regulation, and movement. Moreover, it is the product of the organic integration of guiding techniques, such as qigong, martial arts, and medicine (Jahnke et al, 2010;Yeung et al, 2018;Yang et al, 2022). Regardless of the kind of traditional Chinese fitness exercise, it is based on the theories of yin and yang, zang-fu organs, qi and blood, meridians, and collaterals of traditional Chinese medicine.…”
Section: Introductionmentioning
confidence: 99%